Impact of mashing protocol on the formation of fermentable sugars from millet in gluten-free brewing. (30th March 2023) - Ledley, Andrew J.; Elias, Ryan J.; Cockburn, Darrell W.
Highlights: Amylolytic enzymes are more thermostable in native mashing systems compared to buffered extracts. Enzymes extracted from millet malts should be kept ≤ 60 °C to maintain activity. Coarse grinds reduce enzyme extraction in the mash and introduces processing hurdles. Adding exogenous enzymes can improve sugar production. Starch degradation in a millet mash can be rapid despite low amylase activity. Abstract: The production of fermentable sugars (FS) in gluten-free (GF) brewing is hindered by the high starch gelatinization temperatures of GF malts and lower diastatic power compared to barley malt. Our previous work has demonstrated that starch gelatinization was the primary hurdle, and when decoupled from a single mash phase, high concentrations of FS could be produced. However, more research was required to improve the applicability of GF brewing. In this study, millet was used as a model GF malt demonstrating that despite the low α-amylase and β-amylase activities compared to barley malt ∼ 90 % of the FS (∼110 g/L) could be produced within 40 min. Limitations to enzyme extraction and separation due to coarse milling and lautering initially limited FS by ∼ 30 g/L, requiring additional processing or exogenous enzyme supplements that improved fermentable sugar generation by ∼ 20 g/L. Overall, millet is a promising brewing ingredient, provided appropriate mashing procedures are implemented.